Nonverbal Requesting and Problem-Solving by Toddlers With Down Syndrome - Fidler, Deborah J. (Am J Ment Retard, 2005)
The association between nonverbal requesting (as measured by the Early Social Communication Scales) and problem-solving skills (as measured by an object retrieval task) was examined in 16 toddlers who had Down syndrome, 18 toddlers with developmental disabilities of mixed etiologies, and 19 typically developing infants and toddlers. Toddlers with Down syndrome showed fewer instrumental requests than did those in the typically developing group, but equal numbers of social routine requests. Toddlers with Down syndrome also showed poorer problem-solving strategies and received more help than children in both comparison groups on the object-retrieval task. Results showed a significant association between instrumental requests and problem-solving in the Down syndrome group. Implications for strengthening problem-solving skills in Down syndrome are discussed.